Polish Lymphoma Research Group Experience With Bexarotene in the Treatment of Cutaneous T-Cell Lymphoma. (May 2016) - Sokolowska-Wojdylo, Malgorzata; Florek, Aleksandra; Zaucha, Jan Maciej; Chmielowska, Ewa; Giza, Agnieszka; Knopinska-Posluszny, Wanda; Kulikowski, Waldemar; Prejzner, Witold; Romejko-Jarosinska, Joanna; Paszkiewicz-Kozik, Ewa; Osowiecki, Michal; Walewski, Jan; et al.
Abstract : Bexarotene, a synthetic retinoid licensed for the treatment of refractory cutaneous T-cell lymphoma (CTCL), has been used clinically in Poland since 2007 in 21 patients. The objective of our retrospective, multicenter study was to evaluate our experience with bexarotene therapy, including efficacy, safety, and survival outcomes. We retrospectively identified 21 adult patients who were treated with bexarotene between the years 2007 and 2012. Starting dose of bexarotene was 300 mg/m 2 per day. The analysis included 3 patients with early-stage mycosis fungoides (MF), 16 patients with advanced-stage MF, and 2 patients with Sézary syndrome (SS). The mean duration of therapy with bexarotene was 14.5 months. Use of bexarotene resulted in an overall response rate of 81.0%, although the overall mortality rate was 52.8%. In our study, early-stage CTCL responded better than advanced-stage CTCL (100.0% vs. 77.8%, respectively). The mean time to observable response was 1.8 months, and the mean duration of the response was 16.4 months. Most significant side effects were hyperlipidemia, hypothyroidism, and a bleeding gastric ulcer. Based on the results of our analysis, bexarotene is a valuable tool in the treatment of refractory early-stage CTCL. Although a majority of patients initially responded to therapy, the high mortality rate in the advanced-stage group suggests that bexarotene does not completely resolve the therapeutic problems in all stages of CTCL. Patient stratification for bexarotene treatment may need a thorough reassessment, in that bexarotene may not be an effective drug in the very advanced stages of CTCL.